Quantitative imaging in cell biology - Waters, Jennifer Catherine; Wittmann, Torsten (San Diego, CA Academic Press is an imprint of Elsevier, 2014)
This new volume, number 123, of Methods in Cell Biology looks at methods for quantitative imaging in cell biology. It covers both theoretical and practical aspects of using optical fluorescence microscopy and image analysis techniques for quantitative applications. The introductory chapters cover fundamental concepts and techniques important for obtaining accurate and precise quantitative data from imaging systems. These chapters address how choice of microscope, fluorophores, and digital detector impact the quality of quantitative data, and include step-by-step protocols for capturing and analyzing quantitative images. Common quantitative applications, including co-localization, ratiometric imaging, and counting molecules, are covered in detail. Practical chapters cover topics critical to getting the most out of your imaging system, from microscope maintenance to creating standardized samples for measuring resolution. Later chapters cover recent advances in quantitative imaging techniques, including super-resolution and light sheet microscopy. With cutting-edge material, this comprehensive collection is intended to guide researchers for years to come.--Provided by publisher.
Contents note continued: References -- ch. 26 Adaptive Fluorescence Microscopy by Online Feedback Image Analysis / Rainer Pepperkok -- Introduction -- 26.1.Requirements for Adaptive Feedback Microscopy -- 26.2.Selected Applications -- Acknowledgments -- References -- ch. 27 Open-Source Solutions for SPIMage Processing / Pavel Tomancak -- Introduction -- 27.1.Prerequisites -- 27.2.Overview of the SPIM Image-Processing Pipeline -- 27.3.Bead-Based Registration -- 27.4.Multiview Fusion -- 27.5.Processing on a High-Performance Cluster -- 27.6.Future Applications -- References -- ch. 28 Second-Harmonic Generation Imaging of Cancer / Kevin W. Eliceiri -- Introduction -- 28.1.SHG Physical and Chemical Background -- 28.2.SHG Instrumentation -- 28.3.Collagen Structure as a Biomarker -- 28.4.SHG in Cancer Research -- 28.5.Quantitative Analysis of SHG Images -- Conclusion -- References.
Includes bibliographical references and index.
Keywords: Imaging systems in biology; Microscopy; Electronic books